Methods for inoculation and evaluation of resistance to Macrophomina phaseolina in soybean genotypes - Bizari, Eduardo Henrique [UNESP]; Panizzi, Rita de Cássia [UNESP]; Pedroso Val, Bruno Henrique [UNESP]; Giaretta Azevedo, Cleber Vinicius [UNESP]; Franco, Carolina Andrade [UNESP]; Checchio Mingotte, Fábio Luiz [UNESP]; Prates Coelho, Anderson [UNESP]; da Silva Souza, Jardel [UNESP]; Unêda-Trevisoli, Sandra Helena [UNESP] (Wiley, 2024)
Charcoal rot, caused by Macrophomina phaseolina, is a disease of economic significance in soybean production. The evaluation of this disease is difficult due to the lack of reliable and efficient methods for testing soybean genotypes. This work aimed at investigating different inoculation methods for Macrophomina phaseolina in soybean genotypes to determine the degree of resistance and their use in genetic improvement programs. Infected sorghum seeds, pregerminated seed in culture medium, and infected toothpick test were the methods tested. Colonization by the fungus, determined as a colony-forming unit (CFU), and disease development based on root and stem severity (RSS) were evaluated. There was a good correlation between CFU and RSS (0.87), with the infected sorghum seed method being the most efficient means of inoculating. The results show that PI594302 was the most resistant line regarding the two studied parameters and would be a source of resistance to charcoal rot in breeding programs.
Keywords: charcoal rot; genetic resistance; Glycine max